Transitioning to a virtual post-intensive care rehabilitation service in response to the COVID-19 pandemic: results of multidisciplinary focus-groups - Howroyd, Fiona; Earle, Natacha; Weblin, Jonathan; McWilliams, David; Raven, Mark; Duggal, Niharika A.; Ahmed, Zubair; Veenith, Tonny (Frontiers in Medicine, 2025)
BackgroundTelehealth has vastly expanded since the SARS-CoV-2 (COVID-19) pandemic and has been widely implemented as an efficient, cost-effective and accepted means of health care delivery, including rehabilitation. Although telerehabilitation is recommended across national guidelines, there is a lack of practical guidance to support clinicians with virtual adaptations.AimsThis study aimed to describe the key components of a safe and effective virtual post-intensive-care rehabilitation service, through qualitative exploration.MethodsThis is a qualitative study using a focus-group design based upon grounded theory. This study is nested within a service development project, taking place during the COVID-19 pandemic. Focus groups were held after the first wave of the COVID-19 pandemic with key stakeholders from the physiotherapy and critical care departments of a large tertiary hospital in the United Kingdom. Semi-structured questions were used to guide discussions, led by a facilitator and scribe. Transcripts were thematically analysed using an exploratory inductive approach by two researchers then crosschecked.FindingsThree focus groups were attended by 12 multidisciplinary stakeholders, including six physiotherapists, two administration staff members, two critical-care follow-up nurses and two critical care consultants. Thematic analysis identified seven critical elements for virtual adaptations: (1) safety and risk assessment, (2) assessment and outcome measures, (3) virtual platform, (4) resources and equipment, (5) exercise programme adaptation, (6) exercise monitoring and safety, and (7) privacy and information governance.ConclusionOur findings provide practical recommendations for virtual rehabilitation service development and delivery.